Targeted microbubbles combined with low-power focused ultrasound promote the thrombolysis of acute deep vein thrombosis - Chen, Jianfu; Yang, Yuan; Li, Yunyan; Xu, Lirong; Zhao, Chun; Chen, Qi; Lu, Yongping (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The side effects of conventional therapy for acute deep vein thrombosis (DVT) are severe, with inflammatory reactions playing a pivotal role. It is particularly important to explore new ways of treatment thrombosis by targeting inflammatory factors. Methods: A targeted microbubble contrast agent was prepared using the biotin-avidin method. The 40 DVT model rabbits were established and divided into four groups according to different treatment regimens. The four coagulation indexes, TNF-α, and D-dimer content of experimental animals were measured before modeling and before and after treatment, and the thrombolysis was assessed by ultrasound imaging. Finally, the results were verified by pathology. Results and Discussion: Fluorescence microscopy verified the successful preparation of targeted microbubbles. Among the groups, PT, APTT, and TT in Group II-IV were longer than those in Group I (all p < 0.05). FIB and D-dimer content were lower than those in Group I (all p < 0.05), and TNF-α content in Group IV was lower than that in Group I-III (all p < 0.05). Pairwise comparison before modeling and before treatment and after treatment showed that, after treatment, the PT, APTT, and TT in Group II-IV were longer than those before modeling (all p < 0.05). The contents of FIB and D-dimer were lower than those before modeling and before treatment (all p < 0.05). The content of TNF-α decreased significantly only in Group IV, but increased in the other three groups. Targeted microbubbles combined with Low-power focused ultrasound can reduce inflammation, significantly promote thrombolysis, and provide new ideas and methods for the diagnosis and treatment of acute DVT.